Tantangan Postmodernisme bagi Wacana Teologi Kristen Kontemporer - Ferry Simanjuntak; Yosep Belay; Joko Prihanto (KENOSIS: Jurnal Kajian Teologi, 2022)
This article analyzes the postmodern philosophical ideas of three main thinkers, namely Friederich Nietzsche, Jacques Derrida, and Michel Foucault through which several serious consequences are faced for the study of Christian theology today. Postmodernism's critique and attack on the absolute truth claims of modernism also have an impact on the concept of Christian theology. These impacts result in the dismantling of the authority of God's word, confusion, lack of purpose and meaning in contemporary human life. This research uses a literature study with a descriptive qualitative method. Data analysis uses philosophical hermeneutics which includes interpretation, descriptive and comparative studies. The results of this study indicate that the idea of postmodernism has resulted in: The rejection of the monopoly of truth claims that have an impact on cultural superiority, the emergence of pluralism and relativism, the absence of absolute meaning in the biblical text, and the free play of interpretation of biblical texts. A number of these consequences are challenges that need to be addressed immediately.AbstrakArtkel ini menganalisis gagasan-gagasan filsafat postmodern dari tiga pemikir utamanya yaitu Friederich Nietzsche, Jacques Derrida dan Michel Foucault yang melaluinya sejumlah konsekuensi serius diperhadapkan bagi kajian teologi Kristen masa kini. Kritik dan serangan postmodernisme terhadap klaim kebenaran absolut dari modernisme juga berdampak pada konsep teologi Kristen. Dampak tersebut mengakibatkan terjadinya pembongkaran terhadap otoritas firman Allah, kebingungan, ketiadaan tujuan serta makna hidup manusia kontemporer. Penelitian ini menggunakan studi kepustakaan dengan metode kualitatif deskriptif. Analisis data menggunakan hermeneutika filosofis yang mencakup kajian interpretasi, deskriptif dan komparasi. Adapun hasil penelitian ini menunjukkan bahwa gagasan postmodernisme telah menghasilkan: Penolakan terhadap monopoli klaim kebenaran yang berdampak pada superioritas kultural, munculnya pluralisme dan relativisme, ketiadaan makna absolut pada teks Alkitab, dan permainan bebas interpretasi teks-teks Alkitab. Sejumlah konsekuensi ini merupakan tantangan yang perlu dan segera direspons.